Pengaruh Kerja sama Tim, Disiplin Kerja, Lingkungan Kerja dan Loyalitas Kerja Terhadap Kinerja Karyawan: Studi pada karyawan PT. Amerta Indah Otsuka - Nihayatul Mutimmah; Eko Agus Alfianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This reesearch delved into the individual and combined effects teamwork, work dsipline work environtment and loyalty at PT. Amertaa Indah Otsuka Kejayan. Our methodology employed an explanatory quantitative approach, drawing data from the entire workforce of 216 employees. For data collection, we selected a random sample of 140 employees using the Slovin formula. Information was gathered through questionnaires utilizing a 5-point Likert scale. Prior to analysis, the measurement tools underwent rigorous validity and reliability assessments. To ensure the statistical integrity of our findings, we also conducted normality, multicollinearity, and heteroscedasticity tests, confirming the data adhered to classical assumptions. The t-test results revealed that each factor teaamwork, worrk discipline, work environment, and work loyalty-exerted a unique influence on employee performance. Moreover, the F-test unequivocally demonstrated a collective impact of all these elements at employee performance at PT. Amerta Indah Otsuka Kejayaan.